PD-L1 Improves Motor Function and Alleviates Neuropathic Pain in Male Mice After Spinal Cord Injury by Inhibiting MAPK Pathway - Kong, Fanqi; Sun, Kaiqiang; Zhu, Jian; Li, Fudong; Lin, Feng; Sun, Xiaofei; Luo, Xi; Ren, Changzhen; Lu, Lantao; Zhao, ShuJie; Sun, Jingchuan; Wang, Yuan; et al. (Frontiers in Immunology, 2021)
Background: Traumatic spinal cord injury (SCI) causes severe motor dysfunction and persistent central neuropathic pain (Nep), which has not yet been effectively cured. Programmed cell death ligand-1 (PD-L1) is typically produced by cancer cells and contributes to the immune-suppressive in tumor microenvironment. However, the role of PD-L1 in regulating inflammatory response and Nep after SCI remains unclear. A growing amount of researches have begun to investigate the effect of PD-L1 on macrophages and microglia in recent years. Considering the pivotal role of macrophages/microglia in the inflammatory response after SCI, we proposed the hypothesis that PD-L1 improved the recovery of locomotor and sensory functions after SCI through regulating macrophages and microglia. Methods: The mice SCI model was established to determine the changes in expression patterns of PD-L1. Meanwhile, we constructed PD-L1 knockout mice to observe differences in functional recovery and phenotypes of macrophages/microglia post-SCI. Results: In present study, PD-L1 was significantly upregulated after SCI and highly expressed on macrophages/microglia at the injury epicenter. PD-L1 knockout (KO) mice showed worse locomotor recovery and more serious pathological pain compared with wild-type (WT) mice. Furthermore, deletion of PD-L1 significantly increased the polarization of M1-like macrophages/microglia. Mechanistic analysis revealed that PD-L1 may improve functional outcomes following SCI by inhibiting phosphorylation of p38 and ERK1/2. Conclusions: Our observations implicate the involvement of PD-L1 in recovery of SCI and provide a new treatment strategy for the prevention and treatment of this traumatic condition.